1997
DOI: 10.1038/sj.hdy.6881890
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of head size in the common gull Larus canus in relation to environmental conditions during offspring growth

Abstract: We studied the heritability of head length in a common gull (Larus canus) population breeding in western Estonia. Heritability estimates obtained from offspring-parent regressions were moderate to high and significantly different from zero. Head size might hence respond evolutionarily to phenotypic selection. Offspring-mother and offspring-father regressions yielded similar heritability estimates. This indicated that size-related maternal or paternal effects were absent or weak. Heritability and additive genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…For 0ϩ offspring, higher heritability estimates were obtained in tributary streams than in the main river. Such a pattern, whereby high quality habitat is associated with higher heritability, has been previously supported for many traits in birds (Larsson et al 1997;Merilä 1997;Qvarnströ m 1999) and mammals (Réale et al 1999). Three nonexclusive causes may account for such differences (Falconer 1989): (1) a lower additive variance (V A ) under poorer environmental conditions;…”
Section: Variation Of Heritability As a Function Of Habitat And Male mentioning
confidence: 60%
“…For 0ϩ offspring, higher heritability estimates were obtained in tributary streams than in the main river. Such a pattern, whereby high quality habitat is associated with higher heritability, has been previously supported for many traits in birds (Larsson et al 1997;Merilä 1997;Qvarnströ m 1999) and mammals (Réale et al 1999). Three nonexclusive causes may account for such differences (Falconer 1989): (1) a lower additive variance (V A ) under poorer environmental conditions;…”
Section: Variation Of Heritability As a Function Of Habitat And Male mentioning
confidence: 60%
“…The reduction in similarity during naturally occurring poor conditions was most evident when taking age at recruitment into account; similarity decreased with increasing age at recruitment. Although several recent studies of birds have shown that heritability estimates tend to be higher during favorable conditions (reviewed in Larsson et al 1997;Merila 1997;but see Boag 1983), this is the first study to suggest that this may also be true for a sexually selected plumage trait.…”
Section: Control Enlargedmentioning
confidence: 72%
“…The 'quality' of the annual environment can be described with respect to the focal trait. For example, Larsson et al (1997) explored G!E in the head length of the common gulls, and defined the quality of the annual environment according to the year-specific head growth of the offspring. Alternatively, a measure of population productivity can be used to describe the environment (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The use of BLUPs in a two-step approach ignores the uncertainity involved in generating BLUPs, and using such BLUPs in an animal model falsifies the assumption of independence across individuals needed to generate them in the first place. An RRAM has been used to study G!E in the wild (Wilson et al 2005(Wilson et al , 2006, and is a commonly used method in animal breeding (Lynch & Walsh 1998;Schaeffer 2004;Meyer & Kirkpatrick 2005). In the absence of pedigree information, this framework can also be used if one is interested in modelling phenotypic plasticity (I!E) only (equation (2.1), a random regression phenotypic model, Nussey et al (2007)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation